Online Clothing Shopbots via Web Content Extraction / Nurul Syazwani Ramzi - Ramzi, Nurul Syazwani (2017)
Online shopping has become a huge phenomenon lately. User or customer tends to compare the prices of homogeneous clothing category from different websites of online store before choosing and buying the item. User consumes a lot of time and money in order to compare the prices from multiple websites at one time manually since user needs to visit each of clothing websites. To solve this problem, online Clothing Shopbots via Web Content Extraction is developed so it can help user to reduce the time and money consumed to compare the prices because all the items and prices from multiple websites can be compared in just one website to ease the user or customer.